(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Cervical spondylosis, a prevalent degenerative condition, is characterized by chronic pain, incapacity, and restricted cervical mobility. Manual therapy is commonly utilized in clinical practice, although its effects beyond exercise treatment are unclear. Assess the effects of cervical manual treatment and exercise on the disabilities, pain sensitivity to thermal and pressure stimuli, cervical spine range of motion, and pain thresholds of individuals with cervical spondylosis. The study was a randomized, double-blind clinical trial that included 28 patients with persistent cervical spondylosis. Manual therapy and exercise were administered to one group, while the other group was provided with exercise exclusively. Over the course of three to five weeks, each group participated in therapy sessions six times. The following assessments were implemented: cervical range of motion (ROM), Numeric Pain Rating Scale (NPRS), Neck Disability Index (NDI), pressure pain threshold (PPT), heat pain threshold (HPT), cold pain threshold (CPT), and assessments at baseline, immediately post-intervention, and the final session. Independent t-tests and mixed-model repeated-measures ANOVA were implemented. In comparison to the comparator group, the experimental group demonstrated substantial improvements in cervical range of motion (ROM), disability (NDI), and pain intensity (NPRS) (p < 0.05). The experimental group demonstrated a significant increase in pressure pain threshold, particularly at the cervical spine and C7 dermatome. The categories did not exhibit any substantial differences. The sensitivity to thermal discomfort was consistent across both groups. Significant correlations were observed between improvements in neck dysfunction and reductions in pain severity (r = 0.82, p < = 0.001). Cervical manual therapy and exercise are superior to exercise alone in alleviating pain, enhancing neck function, and increasing cervical mobility in cervical spondylosis patients, despite the fact that they do not alter thermal pain sensitivity.